Upaya Peningkatan Pengetahuan tentang Persiapan Persalinan pada Kehamilan Risiko Rendah - Farizi, Sofia; Amalia, Rize Budi; Astuti, Yuli; Yudanagara, Bani Bacan Hacantya; Novitasari, Selviyani; Mulyaningtyas, Fahmida Cahya; Claresta1, Aurellia Rahma (Yayasan Inspirasi El Burhani, 2025)
Introduction : The rate of cesarean deliveries in Indonesia continues to rise, particularly in major cities such as Surabaya, exceeding the 15% limit recommended by the World Health Organization (WHO). The low rate of Vaginal Birth After Cesarean (VBAC) and the limited autonomy of women in choosing their mode of delivery highlight the need for a new approach. Midwifery Led Care is considered effective in reducing medical interventions and promoting a safe, natural birth experience. Objective : The purpose of this service was to increase women's knowledge about preparing for childbirth by promoting natural birth. Method : This public service was conducted by lectures and an analysis of knowledge changes was conducted through pre-tests and post-tests. The evaluation was carried out by comparing the results of the pre-tests and post-tests. Result : This community service activity demonstrated an increase in pregnant women's knowledge regarding childbirth preparation. Of the 10 participants, all of whom were pregnant in their third trimester, the majority had a high school education (70%). Based on pre- and post-test results, the level of knowledge increased from 80% to 100% after the intervention of education classes and prenatal exercises. These results demonstrate that structured and participatory health education is effective in improving pregnant women's readiness for childbirth, particularly in the context of implementing the concepts of Midwifery-Led Care and natural birth.